2013
DOI: 10.1103/physrevlett.110.013901
|View full text |Cite
|
Sign up to set email alerts
|

Robust Two-Dimensional Spatial Solitons in Liquid Carbon Disulfide

Abstract: The excitation of near-infrared (2+1)D solitons in liquid carbon disulfide is demonstrated due to the simultaneous contribution of the third- and fifth-order susceptibilities. Solitons propagating free from diffraction for more than 10 Rayleigh lengths although damped, were observed to support the proposed soliton behavior. Numerical calculations using a nonlinear Schrödinger-type equation were also performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
108
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 45 publications
1
108
2
2
Order By: Relevance
“…In particular, the analysis has shown that the NLSE produces stable solutions for materials exhibiting an interplay of the focusing third-order and defocusing fifth-order susceptibilities, 0 Re [5,6]. Recently, the stable propagation of (2+1)D spatial solitons in carbon disulfide, CS 2 , supported by this mechanism, has been demonstrated experimentally [7].On the other hand, using resonant nonlinearity in the rarefied gas of three-level atoms, which includes competing cubic and quintic nonlinearities, along with the four-wave mixing (FWM), it was possible to demonstrate the stabilization, on a long propagation distance (~20 diffraction lengths), of various soliton species, including fundamental, dipole, and vortex ones. The FWM in a nonresonant medium (glass) was exploited too to arrest the collapse of (2+1)D quasisolitons [8,9].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, the analysis has shown that the NLSE produces stable solutions for materials exhibiting an interplay of the focusing third-order and defocusing fifth-order susceptibilities, 0 Re [5,6]. Recently, the stable propagation of (2+1)D spatial solitons in carbon disulfide, CS 2 , supported by this mechanism, has been demonstrated experimentally [7].On the other hand, using resonant nonlinearity in the rarefied gas of three-level atoms, which includes competing cubic and quintic nonlinearities, along with the four-wave mixing (FWM), it was possible to demonstrate the stabilization, on a long propagation distance (~20 diffraction lengths), of various soliton species, including fundamental, dipole, and vortex ones. The FWM in a nonresonant medium (glass) was exploited too to arrest the collapse of (2+1)D quasisolitons [8,9].…”
mentioning
confidence: 97%
“…The FWM in a nonresonant medium (glass) was exploited too to arrest the collapse of (2+1)D quasisolitons [8,9]. Furthermore, applying a nonlinearity-management procedure [10], it was possible to observe stable (2+1)D spatial solitons in a composite with suppressed (3) χ but conspicuous focusing (5) χ and defocusing (7) χ susceptibilities [11].…”
mentioning
confidence: 99%
“…A challenging problem is finding still more general physically relevant conditions for the creation of complex 3D modes, such as the hopfions [60], skyrmions (which, similar to hopfions, carry two different topological charges) [61,62], monopoles [63], linked vortex rings, and others. In terms of the experiment, the entire area of multidimensional solitons remains a challenging one, as very few experimental results have been reported, thus far (the latest experimental findings are the creation of (2+1)D optical spatial solitons in media with competing focusing-defocusing cubic-quintic [64] and quintic-septimal [65] nonlinearities, as well as the making of a quasi-stable vortex solitons in an optical medium where nonlinear losses are essential [66]). …”
Section: Discussionmentioning
confidence: 99%
“…In (2+1)D, stable soliton solution of the cubic-quintic NL Schrödinger equation (CQ-NLSE) was predicted by considering the competition between focusing third-order and defocusing fifth-order nonlinearities [18]. The experimental observation of stable (2+1)D fundamental solitons in cubic-quintic media, including a dissipative effect due to the threephoton absorption, was recently reported [19].…”
Section: Introductionmentioning
confidence: 99%